The Role of Occupational Pension Funds in Mauritius - Vittas, Dimitri (World Bank, Washington, DC, 2014)
Mauritius belongs to a select group of developing countries where contractual savings-savings with insurance companies and pension funds-exceed 40 percent of GDP and represent a major potential force in the local financial system. Pension funds account for 75 percent of contractual savings. Contractual savings institutions invest in government securities, housing loans, corporate securities, real estate and bank deposits. They currently hold 35 percent of government securities and also account for 36 percent of total outstanding housing loans.Given their strong demand for long-duration assets, they can stimulate the issue of long-term government bonds (both inflation-linked and zero-coupon) and the development of corporate debentures, mortgage bonds, and mortgage-backed securities.Mauritius has a balanced and well-managed multipillar pension system. In addition to several public components, such as the Basic Retirement Pension, the National Pensions Fund (NPF), the National Savings Fund, and the Civil Service Pension Scheme, there are over 1,000 funded occupational pension schemes that play an increasingly important part in the whole system. The funded schemes are divided into two main groups-those insured and/or administered by insurance companies, and those that are self-administered and are registered with the Registrar of Associations. Coverage of the funded schemes is estimated at about 10 percent of the labor force. Together with the unfunded civil service scheme, occupational pension schemes cover about 100,000 employees or 20 percent of the labor force. All types of pension funds, including the public ones, report low operating costs. This reflects the absence of marketing and selling costs and, in the case of large private pension funds, the assumption of some costs by sponsoring employers. The investment performance of the self-administered funds was less than fully satisfactory in the late 1990s, reflecting poor returns on the local and foreign equity markets. Funds insured or administered by insurance companies as well the NPF performed better during this period because of their heavier allocations in government securities and housing loans. However, over a longer period, the private pension funds probably outperformed the NPF. The regulatory framework, though fragmented, is not unreasonable. It has many important provisions, such as observance of internationally acceptable accounting and actuarial standards and minimum vesting and portability rules, and it does not impose prescribed limits on investments. However, consolidation and modernization of the regulatory framework is required, while supervision, which is currently nonexistent, needs to be developed and to be proactive.